2017
DOI: 10.21511/ppm.15(2-1).2017.09
|View full text |Cite
|
Sign up to set email alerts
|

Barriers to the practice of benchmarking in South African restaurants

Abstract: The main purpose of this study is to find the barriers of benchmarking use in independent full-service restaurants in South Africa. The global restaurant industry entities operate in a highly competitive environment, and restaurateurs should have a visible advantage over competitors. A competitive advantage can be achieved only if the quality standards in terms of food and beverage products, service quality, relevant technology and price are comparable to the industry leaders. This study has deployed a descrip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 25 publications
(25 reference statements)
0
4
0
Order By: Relevance
“…This represents a significant reduction in time, and therefore cost in undertaking a benchmarking project. This finding is likely to be of great interest to organisations as it will reduce many of the barriers to benchmarking that have been reported by previous research (Kleynhans and Roberson, 2017;Panwar et al, 2013). Also of note is that this fast time was not BIJ 28,3 achieved by removing visits to benchmarking partners and replacing them by desktop research; for rapid benchmarking projects, one or two benchmarking visits were included, therefore retaining this most valuable technique for best practice learning.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…This represents a significant reduction in time, and therefore cost in undertaking a benchmarking project. This finding is likely to be of great interest to organisations as it will reduce many of the barriers to benchmarking that have been reported by previous research (Kleynhans and Roberson, 2017;Panwar et al, 2013). Also of note is that this fast time was not BIJ 28,3 achieved by removing visits to benchmarking partners and replacing them by desktop research; for rapid benchmarking projects, one or two benchmarking visits were included, therefore retaining this most valuable technique for best practice learning.…”
Section: Discussionmentioning
confidence: 83%
“…More recent sector-based research indicates that this is still an issue. A study by Kleynhans and Roberson (2017), with 2,699 restaurants participating, identified the four main barriers to benchmarking, which are as follows: 1. It is difficult to adapt anomalous (own) practices to derive benefit from best practices.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, these studies also include adopting and implementing best practices based on the process results (Adebanjo et al, 2010). This information access identifies best practices and partners in this process (Kleynhans & Roberson, 2017). In the same way, in the comparison processes, some barriers have been identified, such as difficulty in the adaptation processes, management of the partners in the process, trust in sharing information, internal expertise for the adaptation of the methods, difficulty in pursuit of resources (Malik et al, 2020).…”
Section: Organizational Learning Theory and Higher Education Institut...mentioning
confidence: 99%
“…The questionnaire was constructed, administered and spread online via Surveymonkey, since this platform has characteristics that enhance the efficacy of the questionnaires themselves. As well as managing the sending out of emails and the respective answers in a practical way, it facilitates export in different formats adaptable to software for statistical analysis of the data [108].…”
Section: Database and Samplementioning
confidence: 99%